THE INFLUENCE OF DIFFERENT STRATEGIES LEARNING OUTCOMES ON THE MATERIAL OPERATIONS IN INTEGRATED NUMBER - Raidani Raidani; Ferry Safriandi (SEAN Institute, 2023)
In this study describes one of the Different Strategies on the Results of the Study of Mathematics Operations of Whole Numbers. The method used in this research is quasi-experiment method. The analysis technique in this study used a t-test to assess the hypothesis. Based on the results of the calculation of the hypothesis test, the t-count value is 0.6071 then consulted to the t-table at a significant level of 0.05 and 35 degrees of freedom, the t-table value is 1.6896. Because tcount < ttable (0.6071 < 1.6896), then H0 is accepted, so there is no difference in math learning outcomes in Different Strategies using the traditional algorithm. Thus learning with Different Strategies has no effect.